Analisis Tingkat Risiko pada Proyek Pembangunan Perumahan Grand Eastern Surabaya dengan Metode Severity Index - Febryan, Daniswara Fawwaz; Tjendani, Hanie Teki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The Grand Eastern Surabaya housing development project is one of the housing projects owned by East Park Regensi which is the second stage of development of the Eastern Park Residence housing. The study aims to identify risks relevant to the Grand Eastern Surabaya housing construction project. The study used validity tests and reliability tests with the help of IBM SPSS software to determine the suitability of risk variables and to know the consistency of the risk variable in the Grand Eastern Surabaya housing construction project. Using the severity index and the probability impact matrix methods, it was found that there are 2 risks with very low categories, 10 risks in low Categories, 4 risks for medium categories and 6 risks of high categories.